Differences in midazolam premedication effects on recovery after short-duration ambulatory anesthesia with propofol or sevoflurane for gynecologic surgery in young patients: A randomized controlled trial. Issue 47 (20th November 2020) - Kim, Hyunjee; Park, Sung-Sik; Shim, Jihye
Abstract: Background: Anxiolytic premedication requires careful consideration owing to potential side effects including delayed recovery after ambulatory anesthesia. We aimed to compare the effect of midazolam on recovery profiles postoperatively, depending on whether propofol or sevoflurane was the primary anesthetic. Methods: We enrolled 226 patients (age, 18–50 years) undergoing ambulatory gynecologic laparoscopic surgery. Patients were categorized into propofol without midazolam (P), propofol with midazolam (MP), sevoflurane without midazolam (S), and sevoflurane with midazolam (MS) groups. As premedication, placebo or 0.02 mg/kg intravenous midazolam was used. The primary outcome was the difference in the time from anesthetic discontinuation to eye opening in response to verbal command. Secondary outcomes included postoperative nausea and pain occurrence and time to reach the discharge score. Results: The time from anesthetic discontinuation to eye opening was longer in the MP group (n = 49) than in the P group (n = 50; P < .001) but was not significantly different between the MS (n = 50) and S groups (n = 49; P = .1). Midazolam premedication did not significantly affect postoperative nausea in the MP group compared with that in the P group ( P = .3) but had a nausea prevention effect in the MS group compared with that in the S group ( P < .001). The time to reach the discharge score was similar in all patients regardless of midazolam administration. Conclusion: In the recovery from short-duration ambulatory gynecologic surgery in young patients, intravenous midazolam premedication showed positive effects on postoperative nausea without affecting the time from anesthetic discontinuation to eye opening with sevoflurane-based anesthesia but prolonged the time from anesthetic discontinuation to eye opening with propofol-based anesthesia. Because this difference between the propofol groups is not clinically significant, the results support midazolam premedication in young women. Further studies assessing larger populations are needed.